Silicon in ultrafresh groundwater: a case study of the Imandra Lake catchment, The Kola Peninsula; E3S Web of Conferences; Vol. 98 : 16th International Symposium on Water-Rock Interaction (WRI-16) and 13th International Symposium on Applied Isotope Geochemistry (1st IAGC International Conference) - Guseva N. V. Natalia Vladimirovna; Kopylova Yu. G. Yuliya Grigorievna; Vorobjeva (Vorobeva) D. A. Darjya Andreevna; Khvaschevskaya A. A. Albina Anatolievna; Evtyugina Z. A. Zinaida (2019, 2019)
Title screen